KERJA SAMA GURU BIMBINGAN DAN KONSELING DENGAN ORANG TUA DALAM MENINGKATKAN MOTIVASI BELAJAR PADA SISWA DI SMK NEGERI 4 ACEH BARAT DAYA - Maysi Fajrianda; Jarnawi; Rizka Heni (FOKUS : Kajian Bimbingan dan Konseling dalam Pendidikan, 2026)
This research aims to describe the picture of weak learning motivation in students at SMK Negeri 4 Aceh Barat Daya, and the forms of cooperation carried out by guidance and counseling teachers with parents in improving student learning motivation. This research used a qualitative approach with descriptive analysis method. Data were collected through observation, semi-structured interviews, and documentation involving one school counselor, five parents, and five students selected through purposive sampling. Data analysis followed three stages: data reduction, data presentation, and conclusion drawing. The findings reveal that students’ learning motivation is weak across all four dimensions of Gowing’s model: achievement drive, commitment, initiative, and optimism. The school counselor has implemented a tiered collaboration with parents through WhatsApp and telephone communication, official written notices, home visits, and individual and group meetings. This collaboration has yielded positive outcomes, particularly in improving student attendance, although it remains largely incidental and reactive. The study recommends developing a more proactive, scheduled, and digitally-supported collaboration program.